Antiviral Effect of Pterocarpus indicus Willd Leaves Extract Against Replication of Dengue Virus (DENV) In Vitro - Beti Ernawati Dewi; Marissa Angelina; lia meilawati; Sri Hartati; Indah Dwiatmi Dewijanti; Mei Ria Santi; Hidayati Desti; Mirawati Sudiro (Journal of Tropical Life Science, 2018)
Dengue hemorrhagic fever (DHF) is major public health problem in tropical and subtropical areas of the world with lack of approved vaccines and effective antiviral therapies. With no current treatment for illness attributed to dengue virus (DENV) infection other than supportive care, therapeutic strategies that use natural extract was developed. Indonesia have many plants that potential for antiviral drµgs such as Pterocarpus indicus Willd (P. indicus). The objective of this study was to determine the effect of P. indicus to inhibit DENV replication. We used a well-differentiated hepatocytes-derived cellular carcinoma cell line (Huh-7 it-1 cells) to determine and select antiviral activity. The toxicity effects were determined by MTT assay. Then, the suppression of DENV replication was determined by Focus assay. Dengue infected cells with DMSO were used as control. We found that crude extract (Pi), hexane (Pi.1) and ethyl acetate (Pi.2) extract showed strong inhibition with high selectivity index (SI) of 1,392; 285.36 and 168.56 respectively. Sub fraction of Pi.1 and Pi.2 still showed strong inhibition with high SI. Further sub-sub fraction of Pi.2 such as Pi.2.12 and Pi.2.12.1 still showed inhibition of DENV replication but there was reduction of SI value. The mechanism experiment of Pi.2.12, we found that Pi 2.12 more profound to inhibit in the post infection stage that entry or pre-infection. We conclude that the sub-fraction of Pi.2.12 has potential antiviral activity against DV infection in vitro. Further studies are still needed to investigate the pure compound of Pi.2.12 that inhibit and have advantages in the future as alternative for treatment of DENV infection.